The Implementation of Sharia Values in Interest-Free Motorcycle Financing of Non-Sharia Cooperatives: A Case Study of the Avicenna Jagakarsa School Teachers and Employees Cooperative - Meta Saputra; Gemala Dewi (University of Darusssalam Gontor, 2025)
This research aims to analyze the implementation of sharia values in interest-free motorcycle financing at a non-sharia financial institution, employing a case study of the Teachers and Employees Cooperative at Avicenna School Jagakarsa. Although not officially labeled as a sharia entity, this cooperative offers a program that eliminates the element of riba (usury/interest). This research employs a qualitative approach using a descriptive analysis method with a single case study design. Data collection was conducted through indepth interviews, observation, and documentation review, which were then analyzed using the Miles and Huberman interactive model. The results indicate that the cooperative's operational practices have adopted the murabahah model by setting a fixed profit margin of 1% per month, this is more competitive compared to conventional institutions, which typically charge approximately 2% per month. Member acceptance is driven by two main factors, the theological factor of avoiding riba for the sake of inner peace, and the economic factor of relatively lower costs. This phenomenon also demonstrates the existence of gradual religious pragmatism, where the substance of anti-usury is prioritized over the perfection of formal contracts. Furthermore, sharia values can be internalized within conventional financial institutions as a solution for more equitable financing, although formal contracts are necessary to guarantee comprehensive sharia compliance.